Penguatan Pengetahuan Hukum Siswa Tentang Hutang Piutang melalui Pinjaman Online Guna Mencapai Keluarga Bahagia Berdasarkan UU Perkawinan - Zaini Munawir S; Abdul Lawali Hasibuan; Amrin Mulia Utama Nasution (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aims to provide knowledge regarding debt-related issues arising from online loans—matters that fall under civil law and frequently trigger disputes within the community, particularly among young people, often due to a lack of understanding regarding legal aspects and available dispute resolution mechanisms. Conducted at SMAN 2 Pangururan in Samosir Regency, this initiative seeks to educate participants on the legalities of online loan agreements from both civil and criminal law perspectives. The material covered includes the fundamental concepts of debt and lending, the various types of loan agreements, and the requirements for a valid contract; furthermore, participants gain an understanding of legal risks, ranging from breach of contract to potential criminal elements such as fraud or embezzlement. The outcomes of this activity serve as a foundational step toward fostering a community that is more legally aware, capable of engaging in lawful and secure transactions, and able to resolve disputes wisely in accordance with applicable regulations.